Best practices for instrument settings and raw data analysis in plant flow cytometry - Koutecký, Petr; Smith, Tyler; Loureiro, João; Kron, Paul (Cytometry. Part A, 2023)
Flow cytometry (FCM) is now the most widely used method to determine ploidy levels and genome size of plants. To get reliable estimates and allow reproducibility of measurements, the methodology should be standardized and follow the best practices in the field. In this article, we discuss instrument calibration and quality control and various instrument and acquisition settings (parameters, flow rate, number of events, scales, use of discriminators, peak positions). These settings must be decided before measurements because they determine the amount and quality of the data and thus influence all downstream analyses. We describe the two main approaches to raw data analysis (gating and histogram modeling), and we discuss their advantages and disadvantages. Finally, we provide a summary of best practice recommendations for data acquisition and raw data analysis in plant FCM.
Keywords: délka genomu; Genome Size; Flow Cytometry; ploidie; kalibrace; Ploidies; Reproducibility of Results; reprodukovatelnost výsledků; Calibration; průtoková cytometrie